2001
DOI: 10.1021/la010552a
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayers That Resist the Adsorption of Proteins and the Adhesion of Bacterial and Mammalian Cells

Abstract: This paper examines the hypothesis that surfaces resistant to protein adsorption should also be resistant to the adhesion of bacteria (Staphylococcus aureus, Staphylococcus epidermidis) and the attachment and spreading of mammalian cells (bovine capillary endothelial (BCE) cells). The surfaces tested were those of self-assembled monolayers (SAMs) terminated with derivatives of tri(sarcosine) (Sarc), N-acetylpiperazine, permethylated sorbitol, hexamethylphosphoramide, phosphoryl choline, and an intramolecular z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
545
3
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 575 publications
(573 citation statements)
references
References 87 publications
14
545
3
4
Order By: Relevance
“…One such approach would be to coat the entire self-assembled 3D microcontainer with a layer of an inert metal (by electrodeposition), oxide (by chemical vapour deposition) or a polymer (by immersion or vapor coating) (Rihova, 2000;Johnston et al, 2005). The surface of noble metals can also be readily modified using a variety of self-assembled organic monolayers that are designed to reduce non-specific adsorption of proteins and subsequent biofilm formation (Ostuni et al, 2001). …”
Section: Cell Encapsulationmentioning
confidence: 99%
“…One such approach would be to coat the entire self-assembled 3D microcontainer with a layer of an inert metal (by electrodeposition), oxide (by chemical vapour deposition) or a polymer (by immersion or vapor coating) (Rihova, 2000;Johnston et al, 2005). The surface of noble metals can also be readily modified using a variety of self-assembled organic monolayers that are designed to reduce non-specific adsorption of proteins and subsequent biofilm formation (Ostuni et al, 2001). …”
Section: Cell Encapsulationmentioning
confidence: 99%
“…235 A range of techniques have been used to micropattern endothelial cells. [236][237][238][239][240][241][242][243] Chen et al 244 found that cell spreading acted as a regulator of proliferation or death in human and bovine capillary endothelial (CE) cells by tightly controlling cell spreading with adhesive microislands of fibronectin; fibronectin was adsorbed on a methyl-terminated alkanethiol SAM, whereas the nonadhesive background consisted of a hexaethylene-glycolterminated alkanethiol SAM (HEG-SAM) that resisted protein adsorption and cell attachment. Cells that were free to spread over large microislands displayed growth, as expected, but the cells that were constrained to limit their spreading to a small island displayed apoptosis.…”
Section: Ve Endothelial Cell Biology On a Chipmentioning
confidence: 99%
“…For example, the hydrogen content of plasma polymer films is low in comparison with the polymer of the corresponding monomer owing to considerable cross-linking [16]. It is therefore highly unlikely that low-fouling plasma polymer films produced via the plasma polymerization of 'glyme' monomers will exactly reproduce the polymer surface chemistry generated from the more commonly used PEG polymer graft surfaces [9,[17][18][19]. Plasma polymer chemistries generated from a particular monomer may vary substantially depending on the operational conditions used (reactor geometry, monomer flow rate, pressure, mode and the strength of power delivery and frequency) [20].…”
Section: Introductionmentioning
confidence: 99%